Konsep Quality Assurance Implementasi dan Implikasinya bagi Penguatan Kelembagaan IAIN Samarinda - Rusdi, Rusdi; Abusyairi, Khairy (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This paper proposed some important points related to the findings of the study. Firstly, Quality assurance provides a concept of a guarantee system to the achievement of a standard quality of IAIN Samarinda. Quality assurance of IAIN Samarinda is a kind of quality system implemented at IAIN Samarinda to fulfill some aspects of quality including: quality standard, quality implementation, quality control, and quality development. Secondly, in the context of internal quality assurance, IAIN Samarinda is providing some quality standards as an adjustment agenda to the condition of IAIN Samarinda. This agenda is now processing and it seems running slowly since there are some problems, such as: unfinished quality standard, the duration of drafting of them, and the agenda of focus group discussion. Thirdly, the guidance of the quality standards of IAiN Samarinda is formally stated by the educational regulation of Indonesian government. IAIN Samarinda is processing to fulfill all the criteria stated by the Indonesian educational regulation system. Fourthly, IAIN Samarinda implements the quality standards by involving the all levels and units of IAIN Samarinda; from top leaders of IAIN Samarinda, faculties, and department under coordinated by the quality assurance department of IAIN Samarinda. Fifthly, the system of quality assurance gives a firm guarantee to the implementation of the internal quality assurance which will give a significant positive effect to develop IAIN Samarinda in terms of applying a certain quality standard which is systematic, measurable, and objective quality.